Novel xylose transporter Cs4130 expands the sugar uptake repertoire in recombinantSaccharomyces cerevisiaestrains at high xylose concentrations - Ribeiro Bueno, Joao Gabriel; Borelli, Guilherme; Ribeiro Correa, Thamy Livia; Fiamenghi, Mateus Bernabe; Jos, Juliana; Carvalho, Murilo de; Oliveira, Leandro Cristante de [UNESP]; Pereira, Goncalo A. G.; Santos, Leandro Vieira dos (Bmc, 2020)
Background The need to restructure the world's energy matrix based on fossil fuels and mitigate greenhouse gas emissions stimulated the development of new biobased technologies for renewable energy. One promising and cleaner alternative is the use of second-generation (2G) fuels, produced from lignocellulosic biomass sugars. A major challenge on 2G technologies establishment is the inefficient assimilation of the five-carbon sugar xylose by engineeredSaccharomyces cerevisiaestrains, increasing fermentation time. The uptake of xylose across the plasma membrane is a critical limiting step and the budding yeastS. cerevisiaeis not designed with a broad transport system and regulatory mechanisms to assimilate xylose in a wide range of concentrations present in 2G processes. Results Assessing diverse microbiomes such as the digestive tract of plague insects and several decayed lignocellulosic biomasses, we isolated several yeast species capable of using xylose. Comparative fermentations selected the yeastCandida sojaeas a potential source of high-affinity transporters. Comparative genomic analysis elects four potential xylose transporters whose properties were evaluated in the transporter null EBY.VW4000 strain carrying the xylose-utilizing pathway integrated into the genome. While the traditional xylose transporter Gxf1 allows an improved growth at lower concentrations (10 g/L), strains containing Cs3894 and Cs4130 show opposite responses with superior xylose uptake at higher concentrations (up to 50 g/L). Docking and normal mode analysis of Cs4130 and Gxf1 variants pointed out important residues related to xylose transport, identifying key differences regarding substrate translocation comparing both transporters. Conclusions Considering that xylose concentrations in second-generation hydrolysates can reach high values in several designed processes, Cs4130 is a promising novel candidate for xylose uptake. Here, we demonstrate a novel eukaryotic molecular transporter protein that improves growth at high xylose concentrations and can be used as a promising target towards engineering efficient pentose utilization in yeast.
Keywords: Xylose; Xylose transporter; Major facilitator superfamily; Saccharomyces cerevisiae; Pentose metabolism; Industrial biotechnology